Optimasi Kapasitas PLTS Berdasarkan Ketersediaan Lahan Rooftop Menggunakan Helioscope - Nofri, Irfan; Rohana, Rohana; Lubis, Sudirman; Nasution, Sawirman (Fakultas Teknik UMRI, 2026)
The increasing demand for electrical energy in buildings requires the utilization of renewable energy as an alternative power source. One of the applicable solutions is the implementation of rooftop photovoltaic (PV) systems. This study aims to optimize the rooftop PV system capacity based on the available installation area at the BKD Building of Tebing Tinggi City using Helioscope software. The research method was carried out through building electrical load data collection, electrical energy requirement analysis, PV system capacity calculation, installation area requirement analysis, rooftop simulation using Helioscope software, and simple economic analysis. The results showed that the total electrical energy demand of the building was 304,212 Wh/day, with motor loads dominating energy consumption by 91% of the total electrical usage. The required PV system capacity to supply the entire building load was 82.393 kWp with a required installation area of 552.08 m². Based on the Helioscope simulation results, the available effective rooftop area was only 346.8 m², indicating that the PV system for supplying the entire building load was not feasible to implement. The optimization results showed that the most optimal PV configuration was supplying electronic and lighting loads with a capacity of 7,777.15 Wp using 79 solar modules and requiring an installation area of 52.93 m². The economic analysis indicated that the proposed PV system has a simple payback period of approximately 11 years, demonstrating its feasibility for long-term implementation in government buildings. This study demonstrates that rooftop validation using Helioscope software is essential to produce a realistic rooftop PV design that matches actual building conditions.